A New Normalization Form Based on a General Unified Normalization Computing for the Gravitational Potential Tensor of Arbitrary Orders. Issue 1 (1st May 2022) - Han, Chao; Dong, Tianshan; Cheng, Ming; Wang, Yu; Liu, Shenggang
Abstract: Taking a general unified recursive algorithm for computing the normalized gravitational potential based on Cunningham's formula into account, the numerical stability of both the recursion for spherical harmonic series and the pre-processing for the spherical harmonic coefficients are discussed. Then a new method of normalizing the associated Legendre polynomial is proposed.